JENIS-JENIS POHON PENYUSUN VEGETASI HUTAN RAWA GAMBUT DI SEMENANJUNG KAMPAR KECAMATAN TELUK MERANTI PROVINSI RIAU - Ripin, .; Astiani, Dwi; Burhanuddin, . (Universitas Tanjungpura, 2017)
Peat swamp forest in Semenanjung Kampar Riau is a unique ecosystem because itÂ has a huge plant diversity and high diversity species. The decreasing of natural forest cover on peat swamp forest Semenanjung Kampar was influenced illegal-logging activities. The purpose of Â this study was to identify the tree species of peat swamp forest vegetation in Â Semenanjung Kampar Teluk Meranti sub-district Riau. The method used in this research was survey purposive determination starting poin. The survey consisted of 5 transect that length at 2 km. The results showed that trees species found in Semenanjung Kampar was 70 trees species, that were classified into 38 famili. Dipterocarpaceae was found with the highest number of species which were Anisoptera marginata Korth, Shorea platicarpa Heim, Shorea teysmanniana Dyer ex Brandis, Shorea uliginosa Foxw, dan Vatica teysmanniana Burck. Overall, the research showed that the peat swamp forest at Semenanjung Kampar is in a good state and to be maintained.Keywords : Dipterocarpaceae, Diversity species, Identification, Peat Swamp Forest.